Single-port-plus-one robot-assisted laparoscopic modified Lich-Gregoir direct nipple ureteral extravesical reimplantation in children with a primary obstructive megaureter - Yufeng He; Yufeng He; Shan Lin; Shan Lin; Xinru Xu; Xinru Xu; Shaohua He; Shaohua He; Huihuang Xu; Huihuang Xu; Guangxu You; Guangxu You; et al. (Frontiers Media S.A., 2023)
PurposeTo introduce a new technique of single-port-plus-one robotic laparoscopic-modified Lich-Gregoir direct nipple ureteral extravesical reimplantation and ascertain its validity in the treatment of pediatric primary obstructive megaureter.MethodsBetween January 2021 and November 2021, we retrospectively analyzed the clinical data of 12 children with primary obstructive megaureter who were admitted to the Department of Pediatric Surgery of Fujian Provincial Hospital. All 12 children were treated with single-port-plus-one robotic laparoscopic Lich-Gregoir direct nipple ureteral extravesical reimplantation. Five of them were female and seven were male, including nine cases were simple obstructive type, while the remaining three cases were obstructive with reflux type. The mean age of the children was 17.33 ± 6.99 (10-36) months and the mean follow-up time was 14.16 ± 1.75 (12-17) months. Changes in preoperative and first-year postoperative parameters were compared.ResultsThe mean operative time for all 12 children was 123.58 ± 10.85 (110-145) min, with a mean internal operative time of 101.42 ± 0.85 (90-120) min, a mean operative bleeding time of 2.42 ± 0.67 (2-4) ml, and a mean hematuria duration of 16.08 ± 1.44 (14-19) h. The mean indwelling catheterization time was 2.25 ± 0.45 (2-3) days and the mean hospitalization time was 3.83 ± 0.39 (3-4) days. At the postoperative first year, the ureteral diameter, calyceal diameter, and anterior-posterior renal pelvic diameter were found to be significantly smaller than at the preoperative period (18.83 ± 3.21 mm vs. 6.83 ± 1.27 mm, 13.99 ± 3.58 mm vs. 3.5 ± 2.90 mm, and 34.92 ± 4.25 mm vs. 10.08 ± 1.88 mm, P < 0.001). There was a significant increase in renal cortical thickness and the percentage of differential renal function (3.63 ± 1.66 mm vs. 5.67 ± 1.88 mm, 33.75 ± 2.77 mm vs. 37.50 ± 1.31 mm, P < 0.001). The resolution rate of obstruction was 100% and no child developed DeNovo vesicoureteral reflux.ConclusionThe technique of modified Lich-Gregoir direct nipple ureteral extravesical reimplantation can help maintain the physiological direction of the ureter and at the same time enhance the effectiveness of antirefluxing in robotic surgery. The design of a single-port-plus-one wound can produce a cosmetic appearance by concentrating and hiding the wound around the umbilicus. This modified reimplantation procedure has the potential to become a promising technique in the robot-assisted treatment of primary obstructive megaureter.